Application of an Acellular Dermal Matrix Allograft (CenoDerm) for Treatment of Multiple Gingival Recession Defects: A Case Report with One-year Follow-up - Neda Moslemi; Mohadeseh Heidari; Mahvash Mousavi Jazi; Mahdieh Daneshmonfared (Tabriz University of Medical Sciences, 2014)
Several techniques and materials have been introduced for the treatment of gingival recession defects. This article reports the case of a 43-year old female patient with chief complaint of esthetic problem, presenting multiple gingival recession defects in anterior maxilla. CenoDerm combined with coronally positioned flap was used for management of six teeth with gingival recession. Complete root coverage was achieved in 66.6% of treated sites in one-year follow-up and the patient was satisfied with the esthetic result. The mean root coverage was 86.0% ± 22.3. The mean recession depth reduction and clinical attachment gain were 1.8 ± 0.8 mm and 2.5 ± 0.6 mm, respectively. According to the